Diarrhoeal prevalence and handwashing practices of children attending early childhood development centres in KwaZulu-Natal, South Africa - Samukelisiwe N. Ntshangase; Shanaz Ghuman; Firoza Haffejee (AOSIS, 2022)
Background: Diarrhoea, a leading cause of childhood morbidity and mortality, spread through contaminated food or water or from person to person, is a major cause of hospitalisation in South African children. Aim: To determine if hygiene practices of parents or guardians and early childhood development centre (ECD) educators contributed to diarrhoea in children attending the centres. Setting: The study was conducted at ECD centres in Mpumalanga Township of KwaZulu-Natal province, South Africa. Methods: A descriptive cross-sectional study was conducted at 10 ECD centres. Parents or guardians (n = 385) and educators (n = 121) answered self-administered questionnaires. Frequencies, bivariate associations and multivariate regression modelling were conducted. Results: The prevalence of diarrhoea in children ≤ 5 years was 67.3%. Most parents or guardians washed their hands after defecating and handling a child's faeces as well as before preparing food. Handwashing after urination was low. Washing of children's hands after these events was lower. Although all educators reported always washing the child's hands after defecating and before handling or eating food, they were less likely to wash the children's hands after urination (p = 0.003). Childhood diarrhoea was associated with the type of toilet, households with pit latrines having a higher prevalence of diarrhoea (p  0.001). It was also associated with washing of children's hands after urination (p = 0.014), before handling or eating food (p = 0.001) and with increased number of children in the household (p = 0.001). Conclusion: In this population, the high prevalence of diarrhoea is related to the number of children in a household and handwashing practices. Contribution: This study highlights the importance of handwashing practices in the prevention of diarrhoea in children.